Microwave-assisted leaching for copper recovery from the chalcopyrite concentrate of Sarcheshmeh copper complex - Saeid Zandevakili; Mohammad Reza Akhondi (International Journal of Mining and Geo-Engineering, 2022)
Microwave applications in mining and process metallurgy have been the subject of many studies over the past two decades. This paper reviews the microwave-assisted leaching of copper from high-grade sulfide concentrate of the Sarcheshmeh copper complex. Response surface methodology (RSM) is used to optimize the leaching process. In this research, leaching experiments were carried out in a multi-mode cavity, and times in the presence of varying concentrations of H2O2 with microwave assistance after the leaching process parameters including type and concentration of the oxidizing agent, NaCl concentration, and leaching temperature, were optimized using Taguchi orthogonal array design method. Conventional leaching experiments were also performed to evaluate the influence of microwave radiation. It has been recognized that microwave technology has great potential to improve the extraction efficiency of metals in terms of both reductions in required leaching time and the recovery of valuable metals. Under the optimized conditions, the leaching efficiencies of copper were 75.3% and 42.5% in 3 hours by microwave assistance and conventional leaching methods, respectively..